Epigenetic Control of Interferon-Gamma Expression in CD8 T Cells - Patrícia S. de Araújo-Souza; Steffi C. H. Hanschke; João P. B. Viola (Journal of Immunology Research)
Interferon- (IFN-) γ is an essential cytokine for immunity against intracellular pathogens and cancer. IFN-γ expression by CD4 T lymphocytes is observed only after T helper (Th) 1 differentiation and there are several studies about the molecular mechanisms that control Ifng expression in these cells. However, naïve CD8 T lymphocytes do not produce large amounts of IFN-γ, but after TCR stimulation there is a progressive acquisition of IFN-γ expression during differentiation into cytotoxic T lymphocytes (CTL) and memory cells, which are capable of producing high levels of this cytokine. Differential gene expression can be regulated from the selective action of transcriptional factors and also from epigenetic mechanisms, such as DNA CpG methylation or posttranslational histone modifications. Recently it has been recognized that epigenetic modification is an integral part of CD8 lymphocyte differentiation. This review will focus on the chromatin status of Ifng promoter in CD8 T cells and possible influences of epigenetic modifications in Ifng gene and conserved noncoding sequences (CNSs) in regulation of IFN-γ production by CD8 T lymphocytes.